Firm–Employee Relationships from a Social Responsibility Perspective: Developments from Communist Thinking to Market Ideology in Romania. A Mass Media Story - Apostol, Oana (Journal of business ethics, 2014)
Firm–employee relationships are dependent on the wider societal context and on the role business plays in society. Changes in institutional arrangements in society affect the perceived responsibilities of firms to their personnel. In this study, we examine mass media discussions about firm–employee relationships from a social responsibility perspective via a longitudinal study in Romanian society. Our analysis indicates how the expected responsibilities of firms towards employees have altered with the changing role of firms in society since the early 1990s. These transformations correspond to the ideological developments, from communist to market-based thinking, which have taken place in post-communist Eastern Europe. More specifically, our study shows how the diminishing expectations of corporate social responsibility (CSR) are linked in mass media to increasingly important talk of human resource management (HRM). HRM is a modern business approach believed to address personnel needs and organisational objectives simultaneously. The congruency of goals in HRM may mistakenly lead to the conclusion that organisations are inherently responsible toward their personnel. We argue that this may not necessarily be the case. HRM, matching well the new free-market ideology in post-communist Eastern Europe, was eagerly embraced in that it defined firm–personnel relationships. In this study, we question whether this was an adequate theoretical perspective for Romanian firms to adopt as it lacks sufficient ethical grounding. We also call for a higher awareness concerning the role of mass media in the management literature, since its current role in constructing the ‘rightness’ and ‘wrongness’ in firm–personnel relationships is hardly considered.